Dialectics Of Academic Freedom and Autonomy In The Process Of Higher Education Integration (On The Example Of The Experience of Uzbekistan) - Kudratova Umida Rakhmatovna (Indonesian Journal Publisher, 2026)
The article analyzes the modern transformation of universities in the context of higher education and science integration, the dialectical nature of the concepts of social conditions and institutional autonomy. The evolution of university development from the Humboldt model to the postclassical period, the transformation of traditional academic values ​​under the requirements of a market economy in globalization are studied. Also, the internal and external factors of the implementation of the principles of academic independence and integrity in national research universities within the framework of the